Ensuring Citizenship Rights: Cooperation and Tensions in the Governance of Urban Community Gardens. Issue 5 (November 2020) - Estrada, M; Kotsila, P; Hörschelmann, K; Lazova, Y; Werner, A
Abstract: The manifold social, cultural and health benefits of urban community gardens have received much attention in the literature on urban ecosystem services and nature-based solutions off late. Despite recognition of these benefits by many city governments, critical scholarship in urban political ecology has, however, also shown that urban community gardens can stand in tension with other municipal agendas, in which economic growth is prioritized over social justice. While highlighting some of these tensions, in this paper we pay particular attention to possibilities for cooperation with municipalities and to the possibilities of promoting more inclusive urban citizenship. In the past, community gardens were frequently set up by municipalities for urban residents to respond to food scarcity and public health issues. Today, they are often still founded in periods of socio-economic crisis either by municipalities or by community actors themselves. We discuss whether and if so, how, such a cooperation may promote substantive citizenship rights, while highlighting some of the tensions that counteract this aim. The paper draws on case studies conducted as part of the EU-Horizon2020-funded project NATURVATION (Grant Agreement 730243) and suggests methods for citizen engagement that municipalities can adopt in order to enhance participation in the cooperative development of urban community gardens.